The Relationship between Air Quality and The Incidence of ARI Respiratory Infections in Communities Around Mining-Industrial Locations (Pomalaa District) and Non-Mining-Industrial Locations (Wundulako District) in Kolaka Regency - Kudus, Musrifa; Sunarsih, Sunarsih; Azizi Jayadipraja, Erwin (Magister Kesehatan Universitas Mandala Waluya, 2024)
Introduction:Initial observation of mining industry community in Kolaka Regency Poor air circulation causes smoke to not be able to fully exit through the chimney, so that the combustion chamber looks dirty and dusty and exits through the existing gaps to the community's residential environment. ISPA is one of the diseases with a fairly high morbidity and mortality rate, so it is necessary to carry out integrated, targeted handling aimed at improving environmental quality. This study is to analyze the relationship between air quality and the incidence of respiratory infections of ISPA in communities around the mining industry location (Pomalaa District) and non-mining industry location in Kolaka Regency. Method:Quantitative research using Descriptive Retrospective research design. The target population in this study is the entire community in the area around the Nickel Mining and industrial centers in Kolaka Regency. Samples were taken using the stratified random sampling method totaling 126 respondents. Result:There is a very strong relationship between the results of air quality measurements of PM10 and CO parameter values ​​with an increase in the incidence of ISPA. While for the PM2.5 air quality value there is a strong relationship, and for other air quality parameters such as SO2, NO2, and O3 there is no relationship with the incidence of ISPA or a moderate or even weak relationship. Conclusion: Reducing the use of private vehicles by providing public transportation, or the company providing employee buses to reduce the intensity of air quality decline due to dense vehicles around mining and non-mining areas.